Analyzing Students with Special Needs' Sense of Humor in Emerald School South Jakarta - Pentury, Helda Jolanda; Rangka, Itsar Bolo (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study collates the current state of knowledge regarding the sense of humor attitude in the social interactions among children with special needs, which aims to explore the current state of knowledge and quality of empirical evidence relating to humor among children with special needs. In the study there were involved 78 students of Emerald School of Cinere in South Jakarta. There were more over 20% students in normal condition and students with special needs were 80%. Research had assessed humor in the classroom and humor expression in different groups including those with autism, down syndrome, and other special needs. This study was designed by using the descriptive qualitative method to analyze, describe, and explain the data. The procedure of data collection was done by observation and filled the questionnaire of the Richmond Humor Assessment Instrument (RHAI). The result of the study showed that there were 47, 08% of favorable criteria, and 52, 92% of unfavorable ones. Based on gender, more boys answered favorable criteria compared to girls. Moreover, boys were dare to express their senses of humor than the girls. The girls showed their shynesses to express their sense of humor. The results of the study showed that the children with special needs in Emerald school had less sense of humor. Furthermore, the role of humor in communication development, social facilitation, creativity, and stigma had all received some limited attention among children with special needs in Emerald School, South Jakarta.